2018
DOI: 10.1016/j.aquaculture.2018.08.014
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate-to-lipid ratio in extruded diets for Nile tilapia farmed in net cages

Abstract: The study evaluated productive and economic performance, physiological parameters and nutritional efficiency in net cage-reared Nile tilapia fed extruded diets containing four carbohydrate (CHO) and lipid (LIP) ratios. The 1280 fish in the trial were sex-reversed male Nile tilapia from the Gift strain (157.54 ± 3.50 g). Fish were randomly distributed into 16 net cages (1.0 m 3 ), with 80 tilapias per cage. The four practical diets were formulated with the same ingredients at different proportions of starch and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…This suggests that different protein levels in the diet might affect the optimal ratio of glucose to lipids for groupers. Related research on tilapia also confirmed this view (Coutinho et al., 2018; Xie et al., 2017). At present, there are still limited studies on CHO:L ratio in groupers.…”
Section: Discussionmentioning
confidence: 56%
“…This suggests that different protein levels in the diet might affect the optimal ratio of glucose to lipids for groupers. Related research on tilapia also confirmed this view (Coutinho et al., 2018; Xie et al., 2017). At present, there are still limited studies on CHO:L ratio in groupers.…”
Section: Discussionmentioning
confidence: 56%
“…Very few studies have been conducted with specific focus on dietary CHO:LIP ratio on tilapia. The few ones who did so observed better yield between the range of 2.0-6.5 g.g -1 (Ali and Al-Asgah, 2001;Coutinho et al, 2018;He et al, 2015;Xie et al, 2017). However, in general studies on the performance of tilapia in response to different levels of dietary carbohydrate and lipid give contradictory results.…”
Section: Discussionmentioning
confidence: 99%
“…Studies indicate that CHO:LIP ratio ranging between 2.0-6.5 g.g -1 provides best yield for tilapia (Ali and Al-Asgah, 2001;Coutinho et al, 2018;He et al, 2015;Xie et al, 2017). Keeping the DP:DE ratio constant and replacing lipid completely with starch leading to CHO:LIP ratio of 20 g.g -1 resulted in poor growth (Xie et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Herein, we recommend gurami sago strain aquaculture in concrete ponds, floating net cages and earthen freshwater ponds for 324 days. According to De Oliveira Continho et al, 52 fish reared in cages can increase the variation in weight production. In contrast, the freshwater cages have been marred by increasing the frequencies of fish mortality, causing negative implications to finances and the environment 23,24,53 .…”
Section: Discussionmentioning
confidence: 99%